Analogia das propriedades de concretos com diferentes cimentos e incorporados de resíduos do porcelanato e scheelita - Costa, Claudia Yanara Meira da (Universidade Federal Rural do Semi-Árido, 2019)
Considering the growing demand for materials in construction, especially for concrete production, researchers have been looking for alternatives to reduce consumption of natural resources as a way to ensure sustainable development. Incorporation of residues from industrial activities presents itself as a beneficial solution to this problem, as well as a sustainable destination for previously useless waste. In that perspective, this work aims to evaluate the properties of concretes produced with different types of Portland cement, partially replacing Portland cement with porcelain polishing residue and sand with scheelite residue, simultaneously. In order to do this, a physical, chemical and mineralogical analysis of the residues was performed and the main characteristics of concrete on its fresh state were investigated, such as consistency and specific mass, and also on its hardened state, such as resistance to axial compression, absorption, porosity, ultrasonic pulses propagation speed and microstructure. Those substitutions caused reduction on the concretes consistency and increase of specific mass on fresh state. On hardened state, improvements in absorption and porosity ratios are highlighted, benefiting the microstructure, as well as a higher ultrasonic pulse speed. A reduction in compressive strength at 28 days is also observed. It is possible to verify the quality and durability of the concrete produced with residues, demonstrating both technical and sustainable viability of the substitutions.
Monografia
Keywords: Propriedades mecânicas; Microestrutura; Propriedades físicas; Sustentabilidade; Atividade pozolânica; Mechanical properties; Physical properties; Microstructure; Pozzolanic reaction; Sustainability; ENGENHARIAS::ENGENHARIA CIVIL